2018
DOI: 10.1088/2040-8986/aaaa56
|View full text |Cite
|
Sign up to set email alerts
|

Quantum formulation for nanoscale optical and material chirality: symmetry issues, space and time parity, and observables

Abstract: To properly represent the interplay and coupling of optical and material chirality at the photonmolecule or photon-nanoparticle level invites a recognition of quantum facets in the fundamental aspects and mechanisms of light-matter interaction. It is therefore appropriate to cast theory in a general quantum form, one that is applicable to both linear and nonlinear optics as well as various forms of chiroptical interaction including chiral optomechanics. Such a framework, fully accounting for both radiation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
81
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(81 citation statements)
references
References 200 publications
0
81
0
Order By: Relevance
“…The corresponding field couples preferentially to the nanohelix's fundamental chiral mode if the sign of the optical chirality in the focal field (dictated by the vorticity of the input field) matches that of the relative phase between the electric and magnetic components of the nanohelix's chiral mode (dictated by the helix's handedness). In contrast to recent studies [21,22], the vorticity of the incoming beam was sensed via dipolar interactions not involving any higher order multipoles. To prove our concept experimentally, we investigated the differential transmission of LG ±1 0 beams tightly focused onto a single plasmonic nanohelix.…”
Section: Resultsmentioning
confidence: 69%
“…The corresponding field couples preferentially to the nanohelix's fundamental chiral mode if the sign of the optical chirality in the focal field (dictated by the vorticity of the input field) matches that of the relative phase between the electric and magnetic components of the nanohelix's chiral mode (dictated by the helix's handedness). In contrast to recent studies [21,22], the vorticity of the incoming beam was sensed via dipolar interactions not involving any higher order multipoles. To prove our concept experimentally, we investigated the differential transmission of LG ±1 0 beams tightly focused onto a single plasmonic nanohelix.…”
Section: Resultsmentioning
confidence: 69%
“…Conversely, in systematically ordered media, (whether the orientational ordering is total or partial), a lack of full rotational symmetry means that chiroptical effects can be anticipated in either chiral or achiral samples [52][53][54]. As was observed in Section III, E1E2 terms cannot contribute to chiroptical effects in isotropic chiral or achiral media.…”
Section: Achiral Mediamentioning
confidence: 99%
“…For a future project we plan to do brain transmission and imaging on a human brain with Alzheimer's disease, focusing on areas that are mainly affected such as hippocampus, cingulate gyrus, and amygdala [36]. In addition, Forbes and Andrews [15][16][17][18] showed dipole and quadrupole have a chiroptical effect associated with OAM with circular dichroism (left and right circular polarization). Afanasev et al [37] have shown that higher multipole transitions exhibit circular dichroism with OAM (ℓ) dependency, in non-chiral atomic matter.…”
Section: Discussionmentioning
confidence: 99%
“…This chiral medium will interact with the electromagnetic field of light by changing its state of polarization; this effect makes the brain a chiral bio-plasma [14]. Structured vector light is expected to interact with chiral matter by coupling with electric dipole, magnetic dipole and quadrupole moments and transitions from Fermi Golden Rule [15][16][17][18]. The underlying unique and complex structure and properties make the brain a "smart tissue"; due to this heterogeneity in the brain, different regions could show dissimilar effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation